PENERAPAN ASAS KEPENTINGAN TERBAIK BAGI ANAK DALAM PELAKSANAAN DIVERSI (Studi Kasus di Cabang Kejaksaan Negeri Deli Serdang di Labuhan Deli) - Irzan Hafiandy; Madiasa Ablisar; Marlina Marlina; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT Law number 11 year 2012 about the criminal justice system of Children mentioned that is the basis of the best interests of the child are all forms of decision-making must always consider survival and flower growing. Decision making always consider survival and growing this flower later becomes the background of the law enforcement agencies especially the Prosecutor in the performance of diversion. The writing is made to cover a few things about how the best interests of the child principle was revealed in legal norms contained in the law criminal justice system of the child, the application of legal norms for the child's best interests principle in the implementation of diversion at the State Attorney's branch of Deli Serdang in Labuhan Deli as well as explain the factors restricting and efforts to overcome the obstacles in the diversion implementation of the best interests of the child principle in the State Attorney's Branch of Deli Serdang in Labuhan Deli. Keywords: The Best Interest of The Child, Diversion, and the Public Prosecutor